(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
As it is known, aviation equipment and methods of its operation are continuously improved in order to solve the problem of flight safety. Modern aircrafts are equipped with more sophisticated automated systems that assist the pilot in the implementation of piloting and navigation functions. At the same time, the introduction of such systems complicates the pilot’s monitoring over the systems operation. Consequently, the breadth of professional erudition and the analytical abilities of the future pilot are of great importance. The issues of readiness to solve problem situations arising in the process of their professional activity, namely in flight are becoming increasingly important. Statistics shows that most fatal accidents are caused by errors in decision-making - 51.6%, while errors in procedural and sensory-motor activities account for 4.6% and 43.8% of fatal accidents. All this is the evidence that the current pilot, for the most part, does not comply with modern requirements for the operation of aircraft fully. Researchers A. Vorona, D. Gander, V. Ponomarenko [8] note the fact that nowadays professional flight school graduates almost have no psychological readiness for the upcoming activities. And their too low professional reliability leads to deficiencies in work, incidents and accidents due to human factor. Although the flying establishments, in general, carry out their functions in training pilots, the training system, mainly based on the experience of the flight methodological work of its developers, often has no scientific substantiation and is not optimal. As a result, the cadets have no sufficiently developed skills that contribute to their readiness to make a competent decision in a problem situation that arises in the process of the performing training flight. The imperfection of the training technology is directly connected to the inability of the flight personnel to analyze the current situation correctly and make the right decision clearly and quickly, on the basis of the information received (pre-flight and instruments readings in flight), available knowledge, skills and abilities.